Law Enforcement Against the Crime of Drinking Alcohol in the Jurisdiction of Labuhanbatu Police Station - Alfiqri Maisyah; Kusno Kusno; Ahmad Ansyari Siregar (Journal of Social Research, 2023)
Basically, a legal norm is part of the legal system, to apply an article in the Criminal Code (KUHPidana). This study aims to find out and analyze law enforcement against criminal offenders of explosive and circulating liquor. As well as knowing and analyzing the modus operandi of criminal offenders of exploiting and distributing liquor. This research belongs to the normative type of research. So it can be known that the modus operandi of the perpetrator of bootleg liquor is put in plastic wrap and sold secretly. Another motive of the perpetrator is due to economic factors and cultural factors. Based on the explanation above, it can be concluded that the modus operandi of the bootleg liquor perpetrator is put in plastic wrap and sold secretly. Another motive of the perpetrator is due to economic factors and cultural factors.